Viscosity development from oat bran β-glucans through in vitro digestion is lowered in the presence of phenolic compounds. Issue 7 (14th March 2022) - Northrop, Grace; D'costa, Adrian S.; Tosh, Susan M.; Bordenave, Nicolas
Abstract : Phenolic compounds have been shown to lower the viscosity and water binding capacity of β-glucans, thereby reducing the digestive viscosity of oats products. Abstract : Dietary fibres have been shown to aggregate and lose viscosity and water binding capacity in solution in the presence of phenolic compounds. This study aimed to verify this observation in a complex grain system containing β-glucans. The viscosity of uncooked and cooked oat bran digested in vitro was measured in the presence of 1–30 mM phenolic acids or flavonoids, and digestograms were modelled to understand the effects of phenolic compounds on the drivers of viscosity. The final viscosity of the digesta, driven by β-glucans, underwent a significant decrease of up to 31% upon the addition of phenolic compounds. To account for the inhibitory activity of phenolic compounds on digestive enzymes, modelling of the digestograms was adjusted with reference to that from previous work. The models suggest that phenolic compounds can simultaneously: (1) slow down the release of β-glucans by slowing down digestion through enzyme inhibition, and (2) decrease the viscosity of solubilised β-glucans, likely through colloidal aggregation as observed in solution before. These in vitro results suggest that the health benefits of oats linked to digestive viscosity of β-glucans may be altered by co-formulation with or co-ingestion of phenolic compounds.